2008
DOI: 10.1183/09031936.00016908
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal suppression in bronchiectasis and the impact of inhaled corticosteroids

Abstract: The present study identified three patients with bronchiectasis receiving inhaled corticosteroids (ICSs) who had symptomatic adrenal suppression secondary to ICS. The prevalence of adrenal suppression is unknown in bronchiectasis. The frequency of adrenal suppression and the impact of ICS use in bronchiectasis patients were examined.In total, 50 outpatients (33 receiving ICSs) underwent a short Synacthen test and completed a St George's Respiratory Questionnaire (SGRQ). Symptoms of adrenal suppression, steroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
0
22
0
2
Order By: Relevance
“…Holme et al identified a high frequency of adrenal suppression associated with ICS treatment in bronchiectasis. 176 A statistically significant increase in adverse effects was reported for high dose ICS in the trial of Martinez et al (P=0.04). 172 A trial of high dose budesonide vs budesonide with formoterol identified a numerical increase in the frequency of local side effects with high dose ICS (pharyngeal irritation, dysphonia and gingivitis) and a single case of pneumonia which is a recognised adverse effect of inhaled corticosteroid treatment in COPD.…”
Section: Sectionmentioning
confidence: 87%
See 1 more Smart Citation
“…Holme et al identified a high frequency of adrenal suppression associated with ICS treatment in bronchiectasis. 176 A statistically significant increase in adverse effects was reported for high dose ICS in the trial of Martinez et al (P=0.04). 172 A trial of high dose budesonide vs budesonide with formoterol identified a numerical increase in the frequency of local side effects with high dose ICS (pharyngeal irritation, dysphonia and gingivitis) and a single case of pneumonia which is a recognised adverse effect of inhaled corticosteroid treatment in COPD.…”
Section: Sectionmentioning
confidence: 87%
“…176 Inhaled fluticasone treatment appeared to double the risk. Adrenal insufficiency was associated with poorer quality of life.…”
Section: Section 19mentioning
confidence: 99%
“…Pre-and post-Synacthen total cortisol concentrations for the entire group, as measured in the original study, 12 …”
Section: Total Cortisol Concentrationsmentioning
confidence: 99%
“…In a small study of 5 PiZZ patients, Wilcke and Dirksen [33] have previously identified the potential benefit of ICS in improving lung function in patients with AATD-related emphysema. However, corticosteroid therapy carries a significant side effect burden, including oral thrush, adrenal suppression [34], and pneumonia [35,36]; hence indiscriminate use could cause harm without therapeutic benefit. Studies have previously shown that blood eosinophil count can be reliably used to direct oral corticosteroid therapy in exacerbations [13] and imply that reduced exacerbation rates are the key benefit for eosinophilic patients [15,16].…”
Section: Discussionmentioning
confidence: 99%